Detection of a local Mycobacterium bovis reservoir using cattle surveillance data. Issue 4 (8th September 2021) - Downs, Sara H.; Ashfield, Stuart; Arnold, Mark; Roberts, Tony; Prosser, Alison; Robertson, Andy; Frost, Susanne; Harris, Kate; Avigad, Rachelle; Smith, Graham C.
Abstract: The incidence of bovine tuberculosis (TB, caused by Mycobacterium bovis ) in cattle has been associated with TB in badgers ( Meles meles ) in parts of England. The aim was to identify badger‐associated M. bovis reservoirs in the Edge Area, between the High‐ and Low‐Risk Areas for cattle TB. Data from badger TB surveys were sparse. Therefore, a definition for a local M. bovis reservoir potentially shared by cattle and badgers was developed using cattle TB surveillance data. The performance of the definition was estimated through Latent Class Analysis using badger TB survey data. Spatial units (25 km 2 ) in the Edge Area were classified as having a reservoir if they had (i) at least one TB incident in at least three of the previous 7 years, (ii) at least one TB incident in a cattle herd confirmed by post‐mortem tests as due to M. bovis infection and not attributable to cattle movements in the previous 2 years and (iii) more confirmed TB incidents than un‐confirmed in the previous 2 years. Approximately 20% of the Edge Area was classified as having a local M. bovis reservoir using the cattle‐based definition. Assuming 15% TB prevalence in Edge Area badgers, sensitivity for the local M. bovis reservoir definition varied from 25.7% [95% credible interval (CrI): 10.7%–85.1%] to 64.8% (95% CrI: 48.1%–88.0%). Specificity was 91.9% (CrI: 83.6%–97.4%). Over 90% of the local reservoir was in stable endemic TB areas identified through previous work and its spatial distribution was largely consistent with local veterinary knowledge. Uncertainty in the reservoir spatial distribution was explored through its recalculation in spatial units shifted in different directions. We recommend that the definition is re‐evaluated as further data on badger infection with M. bovis become available.